Molecular phylogeny of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae) from the Western and Northern Cape Province inferred from mitochondrial DNA sequences - Thembeka Clara Nxele; Jadwiga Danuta Plisko; Tarombera Mwabvu; Oliver Tendayi Zishiri (African Invertebrates, 2020)
Species identification of earthworms using morphology can be challenging and inconclusive as homoplasy in many characters is high. The use of molecular DNA technology, such as the use of conserved regions in mtDNA and nuclear DNA has unravelled the phylogenetic background of several earthworm species. The current study utilised the cytochrome c oxidase subunit I (COI) mitochondrial marker to reconstruct the phylogeny of Kazimierzus Plisko, 2006 species from the Western and Northern Cape provinces of South Africa. Phylogenetic reconstructions were implemented using Bayesian Inference, as well as Maximum Likelihood. Both tree building methods adhered to the monophyly of the majority of the taxa. Results showed that species fell into two clades and validated eleven currently known Kazimierzus species (K. circulatus (Plisko, 1998), K. franciscus (Pickford, 1975), K. guntheri (Pickford, 1975), K. hamerae (Plisko, 1998), K. kleinoodi Nxele & Plisko, 2017, K. nietvoorbiji Nxele & Plisko, 2017, K. nieuwoudtvillensis Nxele & Plisko, 2017, K. occidualis (Plisko, 1998), K. pearsonianus (Pickford, 1975), K. phumlani Nxele & Plisko, 2017, K. sophieae (Plisko, 2002)). Cryptic diversity is evident in K. occidualis with genetic divergence greater than 12% amongst populations. Kazimierzus franciscus and K. ljungstroemi (Pickford, 1975) have a low genetic variability suggesting close relatedness or probably conspecificity. A group of specimens from Clanwilliam are morphologically identical to K. sophieae, but are genetically distinct and may belong to undescribed species. This study demonstrates the importance of integrative taxonomy in earthworms in order to present reliable taxonomic and biogeographic data.